PENGARUH AMELIORAN TERHADAP KADAR Pb TANAH, SERAPANNYA SERTA HASIL TANAMAN BAWANG MERAH PADA INCEPTISOL - Nurjaya Nurjaya; Emona Zihan; M. Sri Saeni (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
The presence of heavy metal in soil can reduce the productivity of soil and the quality of agricultural products. The effort for handling the Pb heavy metal pollution in soil is by adding ameliorant. An experiment was conducted with objectives to study zeolit, organic matter and carbon active evectivenees to plant growth, Pb absorption and solubility of Pb in soils, The research was held in a center of vegetable plant on Tegal district. Randomized completely block design used with three replications at 1.20 m x 4.50 m (5.00 m2). Treatment were control, zeolite (1, 2 and 3 tons ha-1), organic matter (5, 10 and 15 tons ha-1), and active carbon (0.5, 1 and 1.5 tons ha-1). The observed parameters were plant height, amount of tuber at 2 nd, 4th, 6th, and 8th weeks after cultivation, wet weight, and dry weight of leaves and bulb, availibility of Pb (Olsen-EDTA extract) in soil, and Pb adsorption in leaves and bulb of onion. Quantitatively, the ameliorant can reduce Pb adsorption in leaves and bulb of onion. Zeolite treatment with 3 tons ha-1 is more effective to reduce the Pb adsorption in leaves and bulb of onion.